2020
DOI: 10.3389/fimmu.2020.593863
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Interleukin-2-Inducible T-Cell Kinase (ITK) Differentiates GVL and GVHD in Allo-HSCT

Abstract: Allogeneic hematopoietic stem cell transplantation is a potentially curative procedure for many malignant diseases. Donor T cells prevent disease recurrence via graft-versus-leukemia (GVL) effect. Donor T cells also contribute to graft-versus-host disease (GVHD), a debilitating and potentially fatal complication. Novel treatment strategies are needed which allow preservation of GVL effects without causing GVHD. Using murine models, we show that targeting IL-2-inducible T cell kinase (ITK) in donor T cells redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
93
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 23 publications
(94 citation statements)
references
References 56 publications
1
93
0
Order By: Relevance
“…We recently showed that ITK is differentially required for GVHD and GVL ( Mammadli et al., 2020 ). Therefore, we tested whether this distinction depends on the interaction of ITK with SLP76.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently showed that ITK is differentially required for GVHD and GVL ( Mammadli et al., 2020 ). Therefore, we tested whether this distinction depends on the interaction of ITK with SLP76.…”
Section: Resultsmentioning
confidence: 99%
“…The SLP76 Y145 and ITK interaction is involved in signaling pathways that lead to cytokine production by T cell populations, as well as in regulating the development of a distinct, innate-type cytokine-producing T cell population in the thymus ( Atherly et al., 2006 ), referred to as innate memory phenotype (IMP) T cells. CD4 + and CD8 + T cells from SLP76Y145FKI mice express significantly higher CD122, CD44, and Eomes compared to T cells from WT mice on a basal, unstimulated level ( Mammadli et al., 2020 ). Since the activation, expansion, cytokine production, and migration of alloreactive donor T cells to target organs are hallmarks of GVHD ( Henden and Hill, 2015 ; Lynch Kelly et al., 2015 ), efforts to understand signaling pathways that allow separation from GVL will enable us to develop target-specific therapeutic modulators.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations